2020
DOI: 10.48550/arxiv.2002.09172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Star Pattern Fragments: Accessing Knowledge Graphs through Star Patterns

Abstract: The Semantic Web offers access to a vast Web of interlinked information accessible via SPARQL endpoints. Such endpoints offer a well-defined interface to retrieve results for complex SPARQL queries. The computational load for processing such queries, however, lies entirely with the server hosting the SPARQL endpoint, which can easily become overloaded and in the worst case not only become slow in responding but even crash so that the data becomes temporarily unavailable. Recently proposed interfaces, such as T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…To further limit the network overhead, Star Pattern Fragments (SPF) [3] clients send conjunctive subqueries in the shape of stars (star patterns) to the server and process more complex patterns locally on the client. Such conjunctive subqueries can be processed relatively efficiently by the server [58], which results in the transfer of significantly fewer intermediate results than in systems like TPF and brTPF.…”
Section: Client-server Architecturesmentioning
confidence: 99%
See 4 more Smart Citations
“…To further limit the network overhead, Star Pattern Fragments (SPF) [3] clients send conjunctive subqueries in the shape of stars (star patterns) to the server and process more complex patterns locally on the client. Such conjunctive subqueries can be processed relatively efficiently by the server [58], which results in the transfer of significantly fewer intermediate results than in systems like TPF and brTPF.…”
Section: Client-server Architecturesmentioning
confidence: 99%
“…However, as shown in our experimental evaluation in Section 7, LOTHBROK actually decreases the number of intermediate results to be enumerated by up to two orders of magnitude compared to triple pattern-based query executors using the optimization techniques explained above. Furthermore, we apply pagination of large result sets, which related studies [32,68] have already shown can effectively limit the effects of a large number of solution mappings, even for star pattern-based query execution [3].…”
Section: Design and Overviewmentioning
confidence: 99%
See 3 more Smart Citations